The Relationship Between Leukocytes Numbers and Consciousness Level of Craniotomy Patients at The Jemursari Islamic Hospital Surabaya in 2018-2019 - Ainul Rofik; Utami Ambarsari; Hafizh Auliyan Sodali; Misbakhul Munir (Universitas Nahdlatul Ulama Surabaya, 2021)
This study investigates the correlation between leukocyte number and the patient's awareness level after craniotomy surgery, both high (leukocytosis) and low (leukopenia). Several studies reveal that an increase in leukocytes affects mortality rates due to the high level of leukocytes affecting our body's functionalities, including awareness. Previous studies revealed that a leukocyte count exceeding 17.5x106/L was associated with a lower GCS score, a longer hospital stay, and worsening CT scan results, regardless of the type of focal lesion that occurred. This study uses observational methods in the form of retrospective case studies. The data was collected from the medical records of the Operation room at Jemursari Islamic Hospital in 2018-2019 with a sample size of 89. The research was conducted at Jemursari Islamic Hospital Surabaya from May 2018 to August 2019. Data were analyzed using the Spearman correlation test with p <0.05. Results showed no significant relationship between the leukocyte count and the consciousness level of post-craniotomy patients. Future research could estimate the specific effects on the morphology of specific leukocyte cells that are elevated in post-craniotomy patients. This research is expected to provide insight into the effect of leukocytes on consciousness to reduce patient mortality after craniotomy.